Death due to homicidal decapitation – a case report (Journal of Patan Academy of Health Sciences, 2019)
Homicidal decapitation is extremely uncommon. We report a rare case of a 41-year female, from Lalitpur, Kathmandu, Nepal, who was decapitated by her husband in their bedroom with the use of a ''Khurpa'' a sharp local knife.